Development Of Physics Module On Catfish Farming To Foster Students' Entrepreneurial Behaviour - Ridho, Muhammad Rasyid; Guntara, Yudi; Haryadi, Rudi (CV. Dharma Samakta Edukhatulistiwa, 2025)
This study aims to develop a physics learning module based on catfish farming as a contextual approach to teaching static fluid concepts. The module was designed using the 4-D development model (Define, Design, Develop, Disseminate) to enhance students' learning interest and foster entrepreneurial behaviour. The module was evaluated by material and media experts, achieving an average score of 87.90%, indicating a high feasibility level for use. Trial tests with students yielded an average score of 83%, reflecting very positive responses. The module not only aids students in understanding physics concepts more effectively but also promotes critical thinking, innovation, and entrepreneurial skills. By integrating physics with real-world applications such as catfish farming, the contextual approach offers meaningful and relevant learning experiences connected to daily life.